Protection of Reinforced Concrete Structures of Waste Water Treatment Reservoirs with Stainless Steel Coating Using Arc Thermal Spraying Technique in Acidified Water - Ismail, Mohamed; Lee, H.; Park, J.; Singh, J. (mdpi, 2016)
Waste water treatment reservoirs are contaminated with many hazardous chemicals and acids. Reservoirs typically comprise concrete and reinforcement steel bars, and the main elements responsible for their deterioration are hazardous chemicals, acids, and ozone. Currently, a variety of techniques are being used to protect reservoirs from exposure to these elements. The most widely used techniques are stainless steel plating and polymeric coating. In this study, a technique known as arc thermal spraying was used. It is a more convenient and economical method for protecting both concrete and reinforcement steel bar from deterioration in waste water treatment reservoirs. In this study, 316L stainless steel coating was applied to a concrete surface, and different electrochemical experiments were performed to evaluate the performance of coatings in different acidic pH solutions. The coating generated from the arc thermal spraying process significantly protected the concrete surface from corrosion in acidic pH solutions, owing to the formation of a double layer capacitance—a mixture of Cr3+ enriched with Cr2O3 and Cr-hydroxide in inner and Fe3+ oxide on the outer layer of the coating. The formation of this passive film is defective owing to the non-homogeneous 316L stainless steel coating surface. In the pH 5 solution, the growth of a passive film is adequate due to the presence of un-dissociated water molecules in the aqueous sulfuric acid solution. The coated surface is sealed with alkyl epoxide, which acts as a barrier against the penetration of acidic solutions. This coating exhibits higher impedance values among the three studied acidic pH solutions.